(3TQM GdehLRs - (3GdcGRQhfis; (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY HbOQJg LhGgQ YbdjI eLQOI CeG HYO adeG cGf EMJjGL GdfGS Edi GdCMcGe GdWHjI hGdbhGYO GdYdGLjI s
(3BNQgG (B:s
(3hOgf GddhR Ch RHOkG hGSJYed aGPG HGd GdOe abO Cef GdaRY ef GdeGA gPG BNQ TQM GdehLR Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3Jdjg fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1900s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs